Group Decision Making Using Cardinal Social Welfare Functions - Keeney, Ralph L.; Kirkwood, Craig W. (Management Science, 1975)
This paper addresses the problem of constructing a group cardinal social welfare function whose arguments are the individual utility functions of group members. Representation theorems are given which show that the social welfare function is restricted to special forms if certain “reasonable” conditions hold. The appropriateness of these conditions for different types of group decision problems is discussed.